2020
DOI: 10.1021/acsami.0c15462
|View full text |Cite
|
Sign up to set email alerts
|

Large-Area Pulsed Laser Deposited Molybdenum Diselenide Heterojunction Photodiodes

Abstract: Two-dimensional (2D) semiconductors, such as transition-metal dichalcogenides (TMDs), have attracted immense interest due to their excellent electronic and optical properties. The combination of single and multilayered 2D TMDs coupled with either Si or II–VI semiconductors can result in robust and reliable photodetectors. In this paper, we report the deposition process of MoSe2-layered films using pulsed laser deposition (PLD) over areas of 20 cm2 with a tunable band gap. Raman and X-ray diffraction indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…91 It has been reported that a high laser energy density and temperature contribute to the high crystalline orientation of the resulting films, and the stoichiometry and purity of the films can be changed by adjusting the pressure and environment in the deposition chamber. 92…”
Section: Synthesis Process For 2d Tmdsmentioning
confidence: 99%
“…91 It has been reported that a high laser energy density and temperature contribute to the high crystalline orientation of the resulting films, and the stoichiometry and purity of the films can be changed by adjusting the pressure and environment in the deposition chamber. 92…”
Section: Synthesis Process For 2d Tmdsmentioning
confidence: 99%
“…Especially, the stoichiometry of the deposit materials could be retained well because the target species are transferred congruently through laser ablation, in the ultrahigh vacuum. [118,165,166] Seo et al reported growth of continuous WSe 2 film through PLD, in the scale of 1 cm × 1 cm. They varied the number of pulses, and obtained various thickness from monolayer to trilayers (Figure 10b) with a high uniformity and homogeneity, demonstrated by the Raman mapping of the E 1 2g and A 1g modes and the root-mean-square (RMS) roughness of 0.26-0.29 nm.…”
Section: Physical Vapor Depositionmentioning
confidence: 99%
“…The current ( I )–voltage ( V ) curves of the InSe–Si heterojunction are displayed in Figure a. The vdWHs show a significant rectifying effect with a large rectification ratio (RR) of 5000 at small bias voltages of ±1 V. As shown in Figure b, the RR of the 2D–3D InSe–Si vdWHs is superior to those of all other 2D InSe-based heterojunctions ,, , and is comparable to those of most transition-metal dichalcogenide-based 2D–3D heterojunctions ,, measured without a gate voltage. The ideality factor ( n ) is 1.1, indicating that the diffusion current is responsible for the current rectifying behavior of the InSe–Si vdWHs.…”
mentioning
confidence: 92%
“…(a) I - V curves of the InSe-Si vdWHs. (b) Comparison of the RRs of various 2D InSe-based heterojunctions and mixed-dimensional (2D–3D) vdWHs measured without a gate voltage, including InSe–Se, InSe–Te, InSe–AsP, InSe–GaTe, InSe–BP, MoS 2 –InSe, InSe–GaSe, InSe–GeAs, MoS 2 –Si, WS 2 –Si, and MoSe 2 –Si …”
mentioning
confidence: 99%